Effects of therapeutic and aerobic exercise programs in temporomandibular disorder-associated headaches - Molheirinho-Alves, PM (2021)
Objective: To assess the effects of three 8-week exercise programs on the frequency, intensity, and impact of headaches in patients with headache attributed to temporomandibular disorder (TMD). Methodology: Thirty-six patients diagnosed with headache attributed to TMD participated in the study and were divided into three groups of 12 patients: a therapeutic exercise program (G1, mean age: 26.3±5.6 years), a therapeutic and aerobic exercise program (G2, mean age: 26.0±4.6 years), and an aerobic exercise program (G3, 25.8±2.94 years). Headache frequency and intensity were evaluated using a headache diary, and the adverse headache impact was evaluated using the Headache Impact Test (HIT-6). The intensity was reported using the numerical pain rating scale. These parameters were evaluated twice at baseline (A01/A02), at the end of the 8-week intervention period (A1), and 8-12 weeks after the end of the intervention (A2). Results: At A1, none of the G2 patients reported having headaches, in G1, only two patients reported headaches, and in G3, ten patients reported headache. The headache intensity scores (0.3 [95% CI: -0.401, 1.068]), (0.0 [95% CI: -0.734, 0.734]) and HIT-6 (50.7 [95% CI: 38.008, 63.459]), (49.5 [95% CI: 36.808, 62.259]), significantly decreased in G1 and G2 at A1. At A2 headache intensity scores (0.5 [95% CI: -0.256, 1.256]), (0.0 [95% CI: -0.756, 0.756]) and HIT-6 (55.1 [95% CI: 42.998, 67.268]), (51.7 [95% CI: 39.532, 63.802]) in G1 and G2 haven't change significantly. The effects obtained immediately after the completion of the intervention programs were maintained until the final follow-up in all groups. Conclusion: The programs conducted by G1 (therapeutic exercises) and G2 (therapeutic and aerobic exercise) had significant results at A1 and A2.